Disparities in Spawning Times Between in situ and ex situ Pillar Corals - Neely, Karen L.; Lewis, Cindy L.; Macaulay, Kevin A. (Frontiers in Marine Science, 2020)
Contrasts in spawning time between wild and onshore colonies of the pillar coral Dendrogyra cylindrus were conducted by comparing eight years of wild spawning observations with three years of observations on ex situ corals held in outdoor flow-through tanks. Wild colonies exhibited peak spawning 3 nights after the full moon and 90-96 minutes after sunset. Corals held ex situ peaked on night 4 after the full moon, with females continuing to spawn through night 8. Spawning occurred ~50 minutes later than in wild colonies, and the spawning window, particularly for females, was significantly greater. Fragments held ex situ for as few as 10 days exhibited this shift to later spawning, but corals held for greater than one year also exhibited significantly later spawning than those held less than one year. We propose that the wild colonies in Florida exhibit a historic natural spawning cycle. Lunar and solar cues determine date and time, but deviations in full moon from average dates affect time of sperm release. Comparisons with other spawning locations in the Caribbean suggest that sites closer to shore delay spawning until later in the evening. We propose that artificial light is altering the light spectrum that D. cylindrus colonies use to cue spawning time. Colonies held at onshore outdoor facilities, which are subject to high levels of artificial light, also have delayed and expanded spawning windows. The implications of widespread and increasing light pollution on spawning synchrony identify a potential stressor that could inhibit natural reef recovery.